Students' Perceptions of ESP Academic Writing Skills through Flipped Learning during Covid-19 - Salvador Montaner-Villalba (National Research University Higher School of Economics, 2021)
Learners studying English for Specific Purposes (ESP) at University regard writing academic papers as a complex process since they have to consider issues about academic writing conventions as well as ethics. This current research examines university students' perceptions of ESP academic writing within the context of the online learning which emerged due to Covid-19 and, therefore, through the Information and Communication Technologies (ICT) and, particularly, utilizing the Flipped Learning approach as an active learning strategy to enhance ESP academic written competence. To be more specific, we examined how students, in tertiary education, perceived ESP academic writing skills within the field of Business English. The participants are 28 students doing the Degree in Administration and Business Management in a Spanish polytechnic. A mixed method research has been conducted for this current paper since both quantitative as well as qualitative methods were utilized for data collection. Regarding this study, both a questionnaire and a focus group interview were utilized to analyse the data. The outcomes proved that students' perceptions towards academic ESP written competence, using Business English, within the Flipped Learning approach was positive. The major results showed students' awareness of their needs and ESP written requirements. This research concludes with some future research suggestions.